Sustainable tourism and economic growth nexus in Kenya: policy implications for post-Covid-19 - Kipkosgei Bitok (Journal of Sustainable Tourism and Entrepreneurship, 2019)
Purpose: The COVID-19 global pandemic has caused an unprecedented socio-economic impact. It has also raised our awareness of the role sustainability needs to play in our economic activities. This study investigated how sustainable tourism has contributed to economic growth in Kenya. Research Methodology: Eviews 10 software was used to analyze the time-series data. Drawing on data from 1995 to 2020, Johansen co-integration, Granger causality, and regression approaches were used. Results: The study found out that tourism employment and GDP are positively connected to economic growth in Kenya. The causality was unidirectional from economic growth to tourism contribution to GDP and employment, with a long-run linkage of the study determinants. Limitations: Since this research used the secondary sources of data, similar studies in the future may concentrate on the primary data sources to investigate the relationship between tourism employment and economic advancement. Contribution: At the new normal in the post-Covid-19 period, the study suggests that legislators and tourism policymakers should focus on the policies aimed at promoting sustainable tourism. Sustainable tourism should be managed following the three pillars of sustainability. Keywords: Development, Domestic, Moderate, Regional, Scenario